The Role of microRNA in Pathogenesis, Diagnosis, Different Variants, Treatment and Prognosis of Mycosis Fungoides - Wen, Pengfei; Xie, Yao; Wang, Lin (Frontiers in Oncology, 2021)
Mycosis fungoides (MF) is the most common type of cutaneous T-cell lymphoma (CTCL), accounting for approximately 50% of all CTCLs. Although various molecular changes in MF have been described in existing studies, no obvious disease-specific changes have been found thus far. microRNAs (miRs) are short, noncoding RNA molecules that play roles in the post-transcriptional regulation of oncogenes and tumor suppressor genes in various diseases. Recently, there has been rapidly expanding experimental evidence for the role of miRs in the progression, early diagnosis, prognosis prediction for MF. Efforts to improve early diagnosis and develop personalized therapy options have become more important in recent years. Here, we provide an overview and update of recent advances regarding miRs associated with MF. Furthermore, we provide insights into future opportunities for miR-based therapies.